Guide for first time parents with reminder / Nur Farahin Sufian - Sufian, Nur Farahin (2015)
Children are the one who needs so much attention from their parents especially at the infant stage. At the infant stage, parents should pay more attention and be extra cared in order to lay a healthy and strong foundation for a better future of the children. Many first time parents have less information and experiences in handling their babies and tend to make mistakes. These mistakes could affect the growth of the children. Guide for first time parents with reminder mobile application is a series of suggestion in handling the babies which focusing in four main categories which are breastfeeding techniques, food choosing, dental health and vaccination. Reminder feature is implemented only in dental health and vaccination categories only. Agile method development is used as the methodology for this research. It consists of five main phases which are planning, analysis, design, development and testing. For the reminder features in both categories, the dental health and vaccination category respectively, user will need to enter the date and time. Then it will result to a notification pop up to remind the first-time parents about the activities that has been set earlier.